In vivo laser assisted microvascular repair and end‐to‐end anastomosis by means of indocyanine green‐infused chitosan patches: A pilot study. Issue 5 (5th June 2013) - Esposito, Giuseppe; Rossi, Francesca; Matteini, Paolo; Scerrati, Alba; Puca, Alfredo; Albanese, Alessio; Rossi, Giacomo; Ratto, Fulvio; Maira, Giulio; Pini, Roberto
Abstract Background and Objectives Laser‐based repairing techniques offer several advantages respect to standard suturing in microsurgery. In this work we evaluate the applicability and feasibility of two innovative laser‐based approaches for microvascular repair and anastomoses: (1) laser‐assisted vascular repair (LAVR); (2) laser‐assisted end‐to‐end vascular anastomosis (LAVA). All these procedures have been executed by the use of diode laser irradiation and chitosan‐patches infused with Indocyanine Green (ICG). Study Design/Materials and Methods Experiments were performed on 30 rabbits. Twenty animals underwent LAVR and 10 end‐to‐end LAVA procedures. In the LAVR group, a 5‐mm longitudinal cut was performed on the common carotid artery (CCA), then an ICG‐infused chitosan patch was topically applied and laser‐soldered over the arterial lesion. In the LAVA group the end‐to‐end anastomosis was executed on CCA by means of application of the three interrupted sutures and subsequent laser soldering of the ICG‐infused patch. Animals underwent different follow‐up periods (2, 7, 30, and 90 days). At the end of every follow‐up, the animals were re‐anesthetized and a microdoppler analysis was performed in order to check patency of the treated vessels. Then soldered segments were excised and subjected to histological and ultrastructural evaluations. Results At the end of surgery no bleeding from the treated segment was observed; all the treated vessels were patent. At the end of follow‐up periods, no signs of perivascular haemorrhage were found. An intraoperative microdoppler evaluation assessed the patency of all the treated vessels. Histology showed a good reorganization of the vascular wall structures and an early endothelial regeneration was observed by SEM. Conclusions Our study demonstrated the efficacy of laser tissue soldering by means of ICG‐infused chitosan patches for the in vivo repairing of microvascular lesions and end‐to‐end anastomoses. This approach offers several advantages over conventional suturing methods and is technically easy to perform, minimizing the surgical trauma to vessels. Lasers Surg. Med. 45:318–325, 2013. © 2013 Wiley Periodicals, Inc.